Selbstgestaltungs- und Präventionspotenziale hochaltriger Menschen in der stationären Langzeitversorgung - Kruse, Andreas; Becker, Gabriele; Schmitt, Eric (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2019)
Healthcare in inpatient long-term care facilities (nursing homes) should not be limited to medical curative measures, but should also include strengthening social participation, autonomy, self-responsibility and joint responsibility of the residents. Prevention and rehabilitation should therefore be even more integrated into care concepts.This article first introduces various areas of prevention physical activity, nutrition, cognitive competence, psychosocial health, abuse, and freedom-removing measures and then discusses their evidence. Essential for the implementation and the success of such measures is the ability and willingness of people in need of care to engage actively in these therapies; here, appropriate and motivating information plays an important role.Subsequently, geriatric rehabilitation is referred to. In the 2013-2017 empirical study Organization and Rehabilitation for Residents in the Nursing Home to Improve Independence and Participation (ORBIT), 215 people in need of care participated in three-month therapeutic interventions, which were followed by three-months of rehabilitative care. Improvements in mobility and quality of life (Barthel index, QOL-AD) could be demonstrated compared to a control group (n = 28). The results have to be considered against the background of a worsening health and reduced functional capacities in old age. A stronger integration of prevention and rehabilitation services into long-term institutional care is functional for strengthening participation and independence - an important condition for the residents’ certainty that their dignity will be respected, competence and strive for self-responsibility and self-determination.
Gesehen am 18.07.2019